Fallout. Season one [videorecording (DVD)] - Wagner, Graham; Robertson-Dworet, Geneva; Djawadi, Ramin (Amazon MGM Studios, 2025)
Based on one of the greatest video games of all time, Fallout is the story of haves and have-nots in a world in which there's almost nothing left to have. 200 years after the apocalypse, the gentle denizens of luxury fallout shelters are forced to return to the incredibly complex, gleefully weird and highly violent universe waiting for them above.